Promotional activities of Scientific and Technological Information (STI) Services in Indonesia and the Philippines a comparative study - Kadir, Abdul (1984)
This study was designed to identify the techniques and methods of promotional activities of STI services and products in Indonesia and the Philippines, and to compare the level of activity in each country. The administration and management aspect of the promotional activities was also investigated to give a comprehensive view of the activities.